2005
DOI: 10.1111/j.1365-2842.2004.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of marginal bone resorption on stress around an implant – a three‐dimensional finite element analysis

Abstract: Average marginal bone resorption of about 1 mm after the first year of functional loading, which is followed by an annual loss of approximately 0.1 mm, has been reported in stable implants. However, finite element analyses on bone stress around implants have been limited to analysing the bone stress in the absence of any bone resorption. Thus, a three-dimensional finite element analysis was performed to compare the bone stresses in a non-resorption model with those in four models with bone resorption of two de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 27 publications
7
58
0
3
Order By: Relevance
“…[7,18] Reported three-dimensional FEA of dental implants indicate that oblique forces are more destructive than axial forces, and they cause greater stress accumulation in the peri-implant bone than do axial forces. [20,21] Our study clearly showed that an increase in the loading force at an angle to the vertical axis increased the stress distribution in both the implant systems (Table 2), which is in agreement with previous reports. [1,3,18,22] For most single-molar implant-supported prostheses, bone loss occurs as a result of excessive occlusal loading.…”
Section: Methodssupporting
confidence: 82%
“…[7,18] Reported three-dimensional FEA of dental implants indicate that oblique forces are more destructive than axial forces, and they cause greater stress accumulation in the peri-implant bone than do axial forces. [20,21] Our study clearly showed that an increase in the loading force at an angle to the vertical axis increased the stress distribution in both the implant systems (Table 2), which is in agreement with previous reports. [1,3,18,22] For most single-molar implant-supported prostheses, bone loss occurs as a result of excessive occlusal loading.…”
Section: Methodssupporting
confidence: 82%
“…The clinical longevity of these implant systems relies on the mechanical integrity of the prosthesis and implant as well as the ability of peri-implant structures to withstand and positively adapt to the loading forces [31]. Excessive occlusal stress can cause bone resorption or even failure of the implant-bone interface, whereas lack of stress may lead to atrophy or even bone loss [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we simulated the MBL progression levels by decreasing in increments of 1.3 mm. This level was equivalent to several implants of many implant systems [12].…”
Section: Discussionmentioning
confidence: 99%
“…Progression of MBL varied in depth (from 1.3 to 2.6 mm), as models were simulated for analysis (Fig. 2b, c) [12].…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation